New white dwarf stars in the Sloan Digital Sky Survey Data Release 10 - Kepler, Souza Oliveira (2015)
We report the discovery of 9088 new spectroscopically confirmed white dwarfs and subdwarfs in the Sloan Digital Sky Survey Data Release 10. We obtain Teff, log g and mass for hydrogen atmosphere white dwarf stars (DAs) and helium atmosphere white dwarf stars (DBs), and estimate the calcium/helium abundances for the white dwarf stars with metallic lines (DZs) and carbon/helium for carbon-dominated spectra DQs. We found 1 central star of a planetary nebula, 2 new oxygen spectra on helium atmosphere white dwarfs, 71 DQs, 42 hot DO/PG1159s, 171 white dwarf+main-sequence star binaries, 206 magnetic DAHs, 327 continuum-dominated DCs, 397 metal-polluted white dwarfs, 450 helium-dominated white dwarfs, 647 subdwarfs and 6887 new hydrogen-dominated white dwarf stars.